Morfologi Kota Ternate - Maulana Ibrahim (Journal of Science and Engineering, 2018)
Ternate City as an old city and has a long history of experiencing a change in character that damages the authenticity and uniqueness of the city, the heritage of the city and its cultural heritage. This study aims to find the spatial pattern of Ternate city, with the approach of spatial morphology, so that the conditions of the original space and its changes can be found. The method used is literature study in the form of old maps and new maps, comparing changes in space from time to time, analyzing the diachronic and synchronic processes of change to find spatial structures so that they can be used as references in the city's architectural preservation efforts. Keywords: morphology, character, city, Ternate